Hemostasis and Thrombosis in the Oldest Old - Tzoran, Inna; Hoffman, Ron; Monreal, Manuel (Seminars in Thrombosis and Hemostasis, 2018)
There is a growing proportion of the elderly population in the Western world, and these individuals require special considerations regarding a broad variety of aspects, including treatment approaches to illnesses that affect all age groups. The hemostatic system in individuals changes considerably with aging. Specifically, changes in levels of procoagulant and natural anticoagulant factors along with thrombopathy simultaneously create a hypercoagulable state and hemostatic difficulties. Underlying morbidities, such as congestive heart failure, chronic obstructive pulmonary disease, diabetes mellitus, and cancer, increase the risk for venous and arterial thrombosis. This population is also increasingly affected by acquired bleeding disorders, including acquired hemophilia and acquired von Willebrand syndrome, as well as mild congenital bleeding disorders. Real-life data demonstrate that recurrent and fatal venous thromboembolism is the major hemostatic concern in the elderly. The fact that treatment of thrombotic complications increases the bleeding risk also has to be taken into consideration, particularly in the older age group. This remains true in the era of direct oral anticoagulants. In conclusion, maintaining a delicate balance between thrombosis and bleeding risks is the key issue in providing qualified treatment to elderly patients.
Keywords: elderly; thrombosis; bleeding; comorbidities